Delayed-Onset Losartan-Induced Pancreatitis Secondary to an Overdose: A Case Report - Shivam Khatri BS; Steven Chacko BS; Salomon Chamay MD; Simon Kashfi MD; Shorabh Sharma MD (SAGE Publishing, 2023)
Acute pancreatitis is defined as inflammation of the pancreas and is most commonly caused by gallstones and alcohol use. Less commonly, acute pancreatitis can be drug induced from medications that are divided into 5 subgroups (classes Ia-V). The subgroups are determined based on the cases reported, reaction with rechallenge and a consistent period of latency. We describe a case of a 34-year-old female who overdosed on losartan pills in a suicide attempt but developed symptoms of drug-induced acute pancreatitis nearly a week later without gallstones, alcohol involvement, or other drug toxicity.